2012
DOI: 10.1177/003335491212700411
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Test Results and Posttest Counseling at STD Clinics in 24 Health Departments: U.S., 2007

Abstract: Objective. We determined the demographic and HIV test characteristics of tests conducted in CDC-funded sexually transmitted disease (STD) clinics with provision of test results and posttest counseling.Methods. We used CDC's HIV Counseling and Testing System data from 2007 for the 24 U.S. health departments that reported test-level data from STD clinics. We calculated and analyzed newly identified HIV positivity and the percentage of tests with provision of test results and posttest counseling (provision of pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…3 Expanded focus on (re-)linkage for persons previously diagnosed with HIV may have the potential to reduce disparities in HIV care outcomes and incidence outside NYC as well, as SHCs nationwide are a high-volume provider of HIV testing, diagnosis, and linkage services to underserved populations with substantial HIV prevalence. 13,19,28 Despite all patients in our study having received HIV diagnoses at least 12 months before their SHC visit, 7% received an HIV test, suggesting that they did not opt out of testing or inform the provider about a previous diagnosis. These patients were more likely to have been born female, exposed to HIV via heterosexual contact, diagnosed with HIV within the previous 1-3 years, and be accessing clinic services for the first time within a year.…”
Section: Discussionmentioning
confidence: 90%
“…3 Expanded focus on (re-)linkage for persons previously diagnosed with HIV may have the potential to reduce disparities in HIV care outcomes and incidence outside NYC as well, as SHCs nationwide are a high-volume provider of HIV testing, diagnosis, and linkage services to underserved populations with substantial HIV prevalence. 13,19,28 Despite all patients in our study having received HIV diagnoses at least 12 months before their SHC visit, 7% received an HIV test, suggesting that they did not opt out of testing or inform the provider about a previous diagnosis. These patients were more likely to have been born female, exposed to HIV via heterosexual contact, diagnosed with HIV within the previous 1-3 years, and be accessing clinic services for the first time within a year.…”
Section: Discussionmentioning
confidence: 90%
“…29,30 HIV-infected youth testing at STD clinics were more likely to return to receive confirmatory testing than older HIV-infected adults. 31 Engaging young black MSM in the health system, offering HIV-preventative services, and providing routine HIV testing could decrease the number of new infections among the group with the highest HIV incidence.…”
Section: Correlates Of Hiv Infectionmentioning
confidence: 99%
“…These findings are consistent with previous findings indicating that STD clinics serve populations who are disproportionately at risk for HIV. 13,1620 …”
Section: Discussionmentioning
confidence: 99%
“…13,16,17 In addition, they are more likely to reach clients who are younger, male, African American, and heterosexual persons who are at high risk for HIV infection, as well as MSM. 13,18–20 Previous studies have indicated that STD clinics report a higher frequency of HIV testing than other health care settings and are more likely to identify persons who are HIV-positive. 13,20,21 …”
mentioning
confidence: 99%
See 1 more Smart Citation